2019
DOI: 10.18805/lr-4093
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and soil moisture conservation studies of pigeon pea based intercropping systems as influenced by different land configurations

Abstract: A field experiment was conducted to study effect of various land configurations on soil moisture conservation and productivity of pigeonpea at experimental farm of AICRP for dry land Agriculture, V.N.M.K.V., Parbhani during kharif season of 2015 and 2016. Soil of experimental field was medium deep black with low in organic carbon, low in available nitrogen, medium in available phosphorus and high in available potassium.The experiment was laid out in split plot design with three main plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…This might be due to the fact that under favourable soil conditions, the plant accumulates and translocates the photosynthates from source to sink more efficiently which in turn increased yield attributes and yield. Similar results of higher grain yield and straw yield were also reported earlier by Pandey et al, (2018) in blackgram, Garud et al, (2019) in pigeonpea and Halli and Angadi (2019) in cowpea also reported higher grain yield with broad bed method of sowing. All weed management practices had significant effect on yield of clusterbean as compared to weedy check.…”
Section: Crop Establishment Methods and Weed Management Practices On ...supporting
confidence: 90%
“…This might be due to the fact that under favourable soil conditions, the plant accumulates and translocates the photosynthates from source to sink more efficiently which in turn increased yield attributes and yield. Similar results of higher grain yield and straw yield were also reported earlier by Pandey et al, (2018) in blackgram, Garud et al, (2019) in pigeonpea and Halli and Angadi (2019) in cowpea also reported higher grain yield with broad bed method of sowing. All weed management practices had significant effect on yield of clusterbean as compared to weedy check.…”
Section: Crop Establishment Methods and Weed Management Practices On ...supporting
confidence: 90%
“…Similar results of higher grain yield and straw yield were also reported earlier by Pandey et al (2018) in blackgram. Similarly, Garud et al, (2019) and Halli and Angadi S.S. (2019) also reported more grain yield in pigeonpea and cowpea, respectively with broad bed furrow method of sowing. W hereas, the maximum grain yield (1280 kg ha -1 ) was obtained with spraying of pendimethalin 30 EC @ 1.0 kg a.i ha -1 PE fb imazethapyr 10% SL @ 55g ha -1 at 15-20 DAS which was significantly more than other weed management practices (Table 2).…”
Section: Yield Attributes and Yieldmentioning
confidence: 74%